Hedging, managerial ownership and firm value - Zamzamir@Zamzamin, zaminor; Haron, Razali; Abdullah Othman, Anwar Hasan (Emerald Publishing Limited, 2021)
Purpose This study investigates the impact of derivatives as risk management strategy on the value of – Malaysian firms. This study also examines the interaction effect between derivatives and managerial ownership on firm value. Design/methodology/approach The study examines 200 nonfinancial firms engaged in derivatives for – the period 2012–2017 using the generalized method of moments (GMM) to establish the influence of derivatives and managerial ownership on firm value. The study refers to two related theories (hedging theory and managerial aversion theory) to explain its findings. Firm value is measured using Tobin’s Q with return on assets (ROA) and return on equity (ROE) as robustness checks. Findings The study found evidence on the positive influence of derivatives on firm value as proposed by – the hedging theory. However, the study concludes that managers less hedge when they owned more shares based on the negative interaction between derivatives and managerial ownership on firm value. Hedging decision among managers in Malaysian firms therefore does not subscribe to the managerial aversion theory. Research limitations/implications This study focuses on the derivatives (foreign currency derivatives, – interest rate derivatives and commodity derivatives) and managerial ownership that is deemed relevant and important to the Malaysian firms. Other forms of ownership such as state-/foreign owned and institutional ownership are not covered in this study. Practical implications This study has important implications to managers and investors. First is on the – importance of risk management using derivatives to increase firm value, second, the influence of derivatives and managerial ownership on firm value and finally, the quality reporting on derivatives exposure by firms in line with the required accounting standard. Originality/value There is limited empirical evidence on the impact of derivatives on firm value as well as – the influence of managerial ownership on hedging decisions of Malaysian firms. This study analyzes the influence of derivatives on firm value during the period in which reporting on derivatives in financial reports is made mandatory by the Malaysian regulator, hence avoiding data inaccuracy unlike the previous studies on Malaysia. This study therefore fills the gap in the literature in relation to the risk management strategies using derivatives in Malaysia.